Ignorer les mots/ ignorer les maux. Discours et pratiques de silenciations épistémiques dans les consultations médicales du réseau municipal de santé à Franca (Brésil) - Cécile Fontaine (Éducation et Socialisation)
In Brazil, research on access to care in the public health system reveals a number of inequalities in care faced by certain patients - particularly women, the working classes and racialized minorities, during medical consultations. The aim here is to highlight a specific form of prejudicial treatment known as epistemic injustice. Based on observations and consultation’s reporting in health posts, emergency departments and hospitalization services in Franca (Brazil), we will see how these injustices are often co-produced by the existence of negative social prejudices against patients, a lack of awareness of social inequalities in health, a more or less authoritarian exercise of power by the doctor and a rigid application of certain medical procedures. Three forms of 'epistemic silencing' (Dotson, 2011) have been identified: 'not believing', 'not saying' and 'silencing'.